Organization of Hospitals: Essential in Promoting Community Well-Being (International Journal of Preventive Medicine and Health (IJPMH), 2024)
The individuals, belonging to all communities, categories and socio-economic backgrounds are overwhelmed by different types of health problems and illnesses. These are overwhelming to the individuals and they are required to make visits to hospitals. Within hospitals, the medical and health care facilities are required to be made available in order to provide medical treatment to the individuals. The hospital services and overall management are required to be put into practice in a well-ordered manner. The members are required to work in collaboration and integration with each other in carrying out tasks and activities efficiently. In urban communities, these are in a well-developed state, whereas, in rural communities, these are not in a well-developed state. Hence, rural individuals are required to migrate to urban communities in order to get their health problems and illnesses treated. There should be recruitment of well-qualified and experienced medical practitioners and health care specialists. Furthermore, there should be made provision of modern, scientific and innovative methods and materials in the implementation of different types of job duties and responsibilities. As a consequence, individuals will render an important contribution in putting into operation different tasks and activities in a well-ordered and regimented manner. Therefore, organization of hospitals is essential in promoting community well-being. The main concepts that are taken into account are, understanding the meaning and significance of organization of hospitals, factors highlighting the organization of hospitals and measures to be implemented in organization of hospitals in a well-ordered manner.